Two-Year Outcome From Combining Cryoballoon Ablation and Left Atrial Appendage Closure: CLACBAC Study - Ren, Zhongyuan; Zhang, Jingying; Wang, Songyun; Jia, Peng; Li, Xiang; Zhang, Jun; Guo, Rong; Li, Hailing; Li, Shuang; Yang, Haotian; Zheng, Yixing; Meng, Weilun; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: catheter ablation combined with left atrial appendage closure (LAAC) emerges as a promising strategy for atrial fibrillation (AF) patients with high stroke risk or contraindications of oral anticoagulants (OACs). However, the evidence of long-term safety and efficacy of combining procedure using cryoballoon ablation (CBA) with LAAC has been yet insufficient. Methods: From October 2015 to December 2017, totally 76 consecutive non-valvular, drug refractory AF patients who underwent combined procedure of CBA and LAAC were included. Peri- and post-procedural safety and efficacy were evaluated through scheduled follow-up and transesophageal echocardiography (TEE). Results: 74 (97.4%) patients underwent combined procedure achieved instant pulmonary vein isolation and satisfactory LAAC. With a mean follow-up time of 23.7±11.0 month, recurrence of atrial arrhythmia was recorded in 35 (48.0%) patients, and survival analysis showed non-significant higher recurrence in persistent AF (p=0.48). The overall OACs withdrawal rate reached 97.2%, while 1 (1.4%) patient had lethal hemorrhagic stroke on single antiplatelet therapy. For safety concern, the overall mortality was 2.7%, resulted from 1 case of myocardial infarction on OAC and 1 hemorrhagic stroke as mentioned. No other major hemorrhagic events occurred. Among 72 (94.7%) patients who underwent TEE, 1 (1.4%) patient had device related thrombosis and 1(1.4%) had prominent residual flow (>3mm). Both were prescribed with long-term OAC without severe complications occurred. Conclusions: Combining CBA with LAAC in a single procedure achieved considerable long-term safety and efficacy, providing a promising strategy for AF management.